Assessing Differences in Athlete-Reported Outcomes Between High and Low-Quality Youth Sport Programs. Issue 4 (2nd October 2018) - Bean, Corliss; Harlow, Meghan; Mosher, Alexandra; Fraser-Thomas, Jessica; Forneris, Tanya
Abstract : The purpose of this study was to examine differences in athlete-reported outcomes based on sport program quality. Twenty-four sport programs were observed using the Program Quality Assessment in Youth Sport (PQAYS) observation tool. A two-step cluster analysis based on total PQAYS scores revealed two groups (low quality = 16, high quality = 8). Athletes ( N = 324) completed 3 questionnaires related to basic needs support, needs satisfaction, and developmental experiences. Results indicated that athletes in high-quality programs perceived significantly greater opportunities for autonomy, relatedness, and choice, as well as higher perceptions of goal setting and lower negative experiences compared to youth in lower quality programs.